Workplace Diversity and Inclusion: Impact on Employee Productivity and Innovation (International Journal of Food and Nutritional Sciences, 2023)
With the current competitive business world, with its globalization and inclusion, organizations are appreciating that workplace diversity and inclusion (D&I) is something worth trying to succeed. Diversity is the existence of the differences among the employees in regard to gender, age, ethnic group and culture, education and experiences. Inclusion translates to the provision of a conducive atmosphere in which everyone is treated with respect, valued, and considered equal within the workplace. It is the purpose of this research to analyze the impact of diversity and inclusion at workplaces on workplace productivity and innovation of the employees.The research was done in structured questionnaire with 100 respondents who were utilized in the corporate world, with others working in IT, finance and services line. Descriptive statistics and correlation analysis of the gathered data were done. The results will indicate that companies that support and encourage diversity and inclusion have a greater rate of employee performances and innovativeness. Workers in inclusive cultures are more connected, energized and can donate innovative ideas and solutions.The findings validate that D&I has effective influences on individual and team productivity, and it does lead to innovation. The research reveals the importance of organizations to embrace effective diversity and inclusion strategies as the part of human resource management. On the whole, the given paper can be regarded as part of the evidence that inclusive and diverse work environment is crucial to sustainable business development and competitive edge.